Lightworks Envelope Show : An Exhibition Catalog of Correspondence Art. - Friedman, Ken; Crane, Mike (Ann Arbor : Lightworks Magazine Inc., 1979)
This catalog corresponds with an exhibition organized by Lightworks Magazine of approximately 300 pieces of ‘mail-art’. The magazine’s invitation to participate, sent out in a “playful Trompe d’oeil’, proposed the use of its own envelope as the artists’ surface to manipulate and send back; this prompt organized the show, thus creating a satisfying grid of specifically standard No. 10 business envelope works. The published catalog features a forward by Ken Friedman (experimental artist and member of the Fluxus interdisciplinary movement) that expands on the significance of ‘correspondence art’ as an instigator of artistic collaboration and growth beyond individuals’ mediums and sense of themselves as lone creative producers. As a Fluxus artist, Friedman’s interpretation of correspondence art is embedded in its potential as a source of experimentation; the agency of each correspondent to shift and further manipulate the finished product echoes the outcomes of several seminal Fluxus works centered on iterative chance-taking and inquiry.
Lightworks Envelope Show was originally presented to the public in July, 1978 at the Ann Arbor Public Library and was the first correspondence art exhibition in the State of Michigan. The show was reinstalled in Detroit in May, 1979 with the assistance of the Artist Guild of Detroit.
Engels
boek
Keywords: Friedman, Ken